Formulation and Optimization of Quinoa Chickpea Apple Pomace-Based Protein Bar for Protein Energy Malnutrition - Rekha Kaushik (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: Protein-energy malnutrition (PEM) remains a primary global health concern due to limited access to balanced diets in vulnerable populations. The development of protein-rich functional foods offers a sustainable approach to addressing this challenge. Quinoa is a pseudocereal rich in essential amino acids. Materials and Methods: In the presented study, a combination of chickpea and quinoa was utilized to formulate a protein-enriched functional bar. Apple pomace, an agro-industrial by-product, was incorporated to enhance nutritional value and promote waste valorization. Response surface methodology was employed to optimize the formulation, resulting in 11 experimental trials based on protein content and sensory acceptability. Results and Discussion: The optimized bar provided 15.8 g protein and 307.71 kcal/100 g, satisfying both nutritional adequacy and sensory quality parameters. The formulated protein bar has potential in fulfilling daily protein requirements by approximately 25–30% of body weight, depending on the individual’s body weight, thereby contributing to the management of PEM. Conclusion: Future research should focus on clinical and consumer-based trials to evaluate acceptance, efficacy, and long-term health benefits of the developed product.